Host specificity of gastrointestinal parasites in free-ranging sloths from Costa Rica - Vanderhoeven, Ezequiel A.; Florida, Madeleine; Cliffe, Rebecca N.; Guzmán, José; Notarnicola, Juliana; Kartzinel, Tyler R. (PeerJ, 2025)
The diversity and host specificity of gastrointestinal parasites infecting free-ranging sloths is poorly known. We compared gastrointestinal parasites of two sloth species from Costa Rica—three-fingered sloths (Bradypus variegatus) and two-fingered sloths (Choloepus hoffmanni)—for the first time in both a primary forest and an urban habitat. We asked whether host-parasite interactions were predominantly structured by host identity, the habitats in which hosts occurred, or both. Coproparasitology revealed protozoa and nematode eggs from both host species, but cestode eggs were recorded only in C. hoffmanni. We found eight parasitic morphotypes in 38 samples, which matches the total number of these parasites described in sloths over the past 100 years. We found no significant difference in overall parasite richness between sloth species or habitats, but the parasite richness of C. hoffmanni was 2-fold greater in the primary forest vs. urban habitat. As no parasite sharing was observed between sloth species, we found strong and significant differences in parasite composition between host species regardless of habitat. In B. variegatus, we observed eggs of four nematode taxa (Spirocercidae, Subuluroidea, Spirurida, Ascaridida) and cysts of Eimeriidae (Apicomplexa). By contrast, in C. hoffmanni, we observed cestodes (Anoplocephalidae), a different nematode from the family Spirocercidae, and also different cysts of Eimeriidae (Apicomplexa). Many rare taxa were recorded only in samples from the primary forest, and these did not match any sloth parasites that had been previously described in the literature, suggesting that at least some could be undescribed species. Together, these results highlight the paucity of comparative parasitology involving tropical wildlife, the importance of characterizing host-parasite transmission networks, and the potential relevance of intermediate hosts that may be relevant to sloth health.
Keywords: Central America; Cestoda; Three-toed sloth; Two-toed sloth; Nematoda; Parasite communities